Elizabeth Bernholz’s Gazelle Twin: Disguise, Persona and Jesterism - Hayward, Philip; Hill, Matt (The Woman Artist: Essays in memory of Dorota Filipczak, 2024)
The proliferation of low-cost, high-quality, digital production and distribution systems over the last two decades has allowed a range of performers to develop repertoires and careers in non-traditional contexts. While often difficult, the ability to gain traction at the fringes of the (still) highly male-dominated music industry has provided opportunities for female artists such as Grimes and FKA Twigs to achieve commercial success and critical acknowledgement. Although not as well-known as the previously named performers, Elizabeth Bernholz, who adopted the professional alias Gazelle Twin (henceforth referred to as GT) in 2009, has also carved out a distinct niche for herself as a vocalist, electronic music composer, performer and video maker. Over the past 13 years she has explored various personae, including, in the run-up to and aftermath of Brexit, that of a 21st-century jester, turning tropes of traditional Englishness against themselves. This chapter provides an analysis of GT’s personae and related creative outputs. In order to address these, the chapter engages with persona studies and deploys elements of analytical musicology, media studies and cultural studies to analyze GT’s multi-faceted output and the broader cultural contexts she has sought to represent. Writing about an artist such as Bernholz involves a complex negotiation of / switching between the performer’s perception of herself, her perception and representation of her creative persona (which has undergone various transitions) and critical responses to her work. As the chapter outlines, these complex roles and switches are as much a part of the creative entity known as GT as they are explanatory factors behind it.